USE OF ELECTRONIC CIGARETTES BY HEALTH STUDENTS AT A PRIVATE UNIVERSITY IN ANÁPOLIS, GOIÁS (CIPEEX, 2025)
The increase in electronic cigarette use among young people has raised concerns among health professionals and scientific communities. Given this, the objective of this study was to evaluate the use of electronic cigarettes (EC) by health students at a private university in Anápolis, Goiás. This is an observational, descriptive, quantitative study that sought to analyze the prevalence of EC use among university students. The study included university students duly enrolled in courses in aesthetics and cosmetics, physical education, nursing, pharmacy, physical therapy, medicine, nutrition, dentistry, and psychology, who were 18 years of age or older, agreed to participate in the study, and consented to the Free and Informed Consent Form (FICF). Of the 444 questionnaires analyzed, 59 individuals in the health field use ECs. Most are female (66.1%), white (66.1%), and between 21 and 24 years old (54.2%). In addition, most have a very low degree of dependence. The reasons that most lead them to use cigarettes were because they like them and find them relaxing, and the place where they are most used is in bars and at parties. It is concluded that identifying the main groups, reasons, and places where CE are used favors the promotion of more effective prevention strategies to reduce the consumption of these products.
Keywords: Electronic nicotine delivery system; Health science students; Smoking